Direction of Arrival Estimation of Meteors Echoes using Array Radio Antennas - Akeab, Imad K.; Bekheet, Yasser Chasib; Al Najm, M. N. (Iraqi Journal of Science, 2024)
Array antennas have an interesting role in the radio astronomy field. The array antennas allow astronomers to obtain high-resolution signals with high sensitivity to weak signals. This paper estimates the meteors’ positions entering the Earth’s atmosphere and develops a simulation for array antenna radar to analyze the meteor’s echoes. The GNU radio software was used to process the echoes, which is a free open-source software development toolkit that provides signal processing blocks to implement in radio projects. Then, the simulation determines the azimuth and elevation of the meteors. An improved Multiple Signal Classification (MUSIC) algorithm has been suggested to analyze these echoes. The detected power of each meteor echo has a Doppler frequency shift due to the high speed of the meteors, which impacts the accuracy of the Direction of Arrival (DOA) estimation. The Doppler shift was considered in this simulation, and the results showed that the suggested method has low complexity and high resolution and can estimate the meteors’ position with the minimum error.